Essential oils from Amorpha fruticosa against hepatocellular carcinoma based on network pharmacology - Yixian Liu; Xiaojun Zhang; Jiacong Hao; Ying Zhao; Min Zou; Huiping Chen; Jintao Zhang (BMC Complementary Medicine and Therapies)
Abstract Background Amorpha fruticosa was used for treating burn, ambustion, carbuncle, and eczema in the traditional Chinese medicine. Although more and more attention has been paid to its biological activity recently, the antitumor activities of the essential oils (EOs) extracted from its leaves (AFLEO) and flowers (AFFEO), and their molecular mechanisms have never been reported up to now. The objective of present study was to examine the chemical compositions of AFLEO and AFFEO, then investigate the effects and pharmacological mechanism of EOs against hepatocellular carcinoma (HCC). Methods The chemical compositions of EOs were examined using gas chromatography-mass spectrometry (GC-MS). The inhibitory effect of the EOs on HCC was evaluated by MTT assay. The detected components of AFLEO and AFFEO were performed ADME screening to examine their drug-likeness. Then a PPI network, compound-target network, compound-target-pathway network, gene ontology, and KEGG enrichment for HCC were applied to identify the targets and pathways for AFLEO and AFFEO against HCC. Molecular docking of the main components and their targets was performed to predict the binding affinity. Western blotting was used to verify the results. Results 30 components were identified from AFLEO, while 22 components from AFFEO. Both AFLEO and AFFEO inhibited the proliferation of HCC cells in a time and dose-dependent manner. 10 compounds of AFLEO and 9 compounds of AFFEO were screened out for further analysis. 28 hub targets of AFLEO and 40 hub targets of AFFEO were detected by PPI network. KEGG analysis revealed that pathways in cancer, chemical carcinogenesis - receptor activation and proteoglycans in cancer were related to the EOs against HCC. Molecular docking confirmed that the main component of the EOs has high affinity to the targets of HCC. Conclusions AFLEO and AFFEO may suppress HCC by acting on multiple targets and regulating multiple pathways.